Poll Workers and the Challenges of Election Management at the Ground Level - Tomasz Czapiewski (Polish Political Science Yearbook, 2025)
This article provides a comprehensive overview of the critical role poll workers play in election administration and the various challenges they face. It synthesizes existing research on poll workers, focusing on their recruitment, training, and election day duties. The study highlights the significance of poll workers as frontline representatives of the electoral system, directly impacting voter experiences and trust in the democratic process. Key findings relate to the increasing complexity of electoral tasks, which require poll workers to possess not only clerical skills but also managerial and technical competencies. Challenges in recruitment and training persist, with many countries struggling to find sufficient numbers of qualified individuals. The article concludes with recommendations for improving recruitment strategies, enhancing training methodologies, addressing political challenges, adapting to technological changes, and standardizing procedures. It also identifies areas for further research, including the long-term consequences of increasing professionalization in electoral work and the role of poll workers in combating misinformation and maintaining public confidence in elections. This comprehensive examination of poll workers’ roles and challenges provides valuable insights for election administrators, policymakers, and researchers working to enhance the integrity and efficiency of electoral processes.